Twelve Tips for Utilizing Residency Program Social Media Accounts for Modified Residency Recruitment - Rakhee K. Bhayani; Laurel Fick; Dawn Dillman; Dink A. Jardine; Amy S. Oxentenko; Avital O'Glasser (MedEdPublish, 2020)
Social media use across the health professions has significantly expanded in recent years. Specific attention has been paid to both the value of social media use in graduate medical education with residency program twitter accounts. More recently, social media has been examined for its role in supporting the rapid expansion of information exchange and connection across digital and virtual platforms during the COVID-19 pandemic. With the ongoing response to the pandemic, the 2020-2021 residency application cycle is anticipated to be a completely virtual interview process. Here, we draw from our collective experiences managing, maturing, and maximizing social media accounts for residency programs and GME to provide practical tips for using social media for the upcoming virtual interview season.